2023
DOI: 10.1002/jmri.28778
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Quantitative MRI of Peripheral Nerves in the Leg: A Reliability Study

Abstract: BackgroundPatients with polyneuropathies typically have demyelination and/or axonal degeneration in peripheral nerves. Currently, there is a lack of imaging biomarkers to track the changes in these pathologies.PurposeTo develop and evaluate the reliability of a multiparametric quantitative magnetic resonance imaging (qMRI) method of peripheral nerves in the leg.Study TypeProspective.SubjectsSeventeen healthy volunteers (36.2 ± 13.8 years old, 9 males) with 10 of them scanned twice for test–retest.Field Strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Indeed, the research article does not conclude that qMRI is sensitive to myelin and axonal pathologies. 2 Instead, our main conclusion was that the proposed metrics were repeatable and may be viable monitoring biomarkers. Furthermore, none of the limitations mentioned in the commentary 1 are associated with the research article.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…Indeed, the research article does not conclude that qMRI is sensitive to myelin and axonal pathologies. 2 Instead, our main conclusion was that the proposed metrics were repeatable and may be viable monitoring biomarkers. Furthermore, none of the limitations mentioned in the commentary 1 are associated with the research article.…”
mentioning
confidence: 89%
“…In this note, we respond to the commentary, 1 which concluded that imaging methods such as quantitative MRI (qMRI) can only be supplementary to the conventional diagnostic methods such as history, clinical exam, nerve conduction studies, electromyography, and nerve biopsies. More specifically, the commentary stated the following related to our recent publication 2 : 1) the "conclusion" that qMRI is sensitive to myelin and axonal pathologies is not supported by the healthy subject data presented by Chen et al 2 ; 2) the diagnosis of polyneuropathies should rely on the conventional electrophysiological methods rather than imaging procedures in polyneuropathies that only have functional abnormalities; 3) qMRI may not be used as a diagnostic biomarker because demyelination and axonal loss are often present simultaneously in polyneuropathies; 4) imaging biomarkers cannot differentiate information from motor, sensory, or autonomic fiber impairment; and 5) imaging methods cannot provide information of the involvement of large fibers, small fibers, or both.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…
We read with interest the article by Chen et al about a study on the reliability of multiparametric, quantitative magnetic resonance imaging (qMRI) of lower limb peripheral nerves in 17 healthy volunteers. 1 It was found that the qMRI parameters magnetization transfer (MT) ratio, MT saturation index (MTsat), T2*, T1, proton density (PD), fractional anisotropy (FA), and mean/axial/radial diffusivities (MD, AD, and RD) had a good-to-excellent test-retest agreement and demonstrated a pattern of distal-to-proximal changes of an increased nerve MTsat and FA, and a decreased nerve T1, PD, MD, and RD, as well as a significantly increased muscle fat fraction. 1 It was concluded that multiparametric qMRI of peripheral nerves is highly reproducible and sensitive to myelin and axonal pathologies.
…”
mentioning
confidence: 99%